The chronology of third molar mineralization by digital orthopantomography. (October 2016) - Maled, Venkatesh; Vishwanath, S.B.
Abstract: The present study was designed to determine the chronology of third molar mineralization to establish Indian reference data and to observe the advantages of digital orthopantomography. Therefore, a cross-sectional study was undertaken by evaluating 167 digital orthopantomographs in order to assess the mineralization status of the mandibular third molar of Caucasian individuals (85 males and 82 females) between the age of 14 and 24. The evaluation was carried out using the 8-stage developmental scheme of Demirjian et al (1973). The range, mean age, standard deviation and Student t -test are presented for each stage of mineralization in all four quadrants. Statistically significant differences between males and females were not found for all four third molars. All the individuals in this study with mature third molar were at least 18 years of age. For medicolegal purposes, the likelihood of whether an Indian is older than 18 years or not was determined. The advantage of digital orthopantomography in the interpretation of the tooth mineralization over the traditional method was acknowledged. Highlights: Study analyze the stage of maturity of the third molars by means of digital OPG. The Demirjian et al scheme is used to assess the mineralization status in Caucasians. Probability of an Indian to be at least 18 years is 100% certain for both sexes. For medicolegal purposes, the likelihood of an Indian to be 18 years was determined. The method can therefore be considered, a valid aid in estimating legal adulthood.